COVID-19 associated coagulopathy: Thrombosis, hemorrhage and mortality rates with an escalated-dose thromboprophylaxis strategy. Issue 196 (December 2020) - Daughety, Molly M.; Morgan, Andrew; Frost, Erin; Kao, Chester; Hwang, Joyce; Tobin, Rachel; Patel, Bhavik; Fuller, Matthew; Welsby, Ian; Ortel, Thomas L.
Highlights: COVID-19 patients are at increased risk of thromboembolic complications. Escalated-dose thromboprophylaxis may help reduce the rate of thromboembolic events. The bleeding risk is highest for patients treated with therapeutic anticoagulation.